(untitled) (Eurasian Scientific Herald, 2023)
In learning English language, there are integrated skill to be mastered by the learners such as: Speaking, Listening, Reading, and Writing. In teaching language for student can’t be separated from speaking activities. It is because speaking is one of the important factors in doing conversation in the class. According to Brown (2004:140), “speaking is a productive skill that can be directly and empirically observed, those observations are invariably colored by the accuracy and effectiveness of a test-taker’s listening skill. Which necessarily compromises the reliability and validity of an oral product test”. For this case, student should master several speaking components, such as: comprehension, pronunciation, grammar, vocabulary and fluency